Evaluation of a New Powerful Bone-Anchored Hearing System: A Comparison Study - Bosman, Arjan J.; Snik, Ad F.M.; Hol, Myrthe K.S.; Mylanus, Emmanuel A.M. (Journal of the American Academy of Audiology, 2013)
Background: The recent introduction of digital hearing aid technology for bone-conduction devices employing percutaneous stimulation may be beneficial for patients with conductive and mixed hearing loss and single sided deafness.Purpose: Performance of a recently released sound processor for bone-anchored implants, the Ponto Pro Power from Oticon Medical (bone-conduction device 2 [BCD2]), was compared with that of the Baha Intenso from Cochlear (bone-conduction device 1 [BCD1]).Research Design: Direct comparison of the subject's own device (BCD1) with the new device (BCD2) was examined in a nonrandomized design. Subjects were initially tested with BCD1. BCD2 was tested after a 4 wk acclimatization period.Study Sample: Eighteen subjects with mixed hearing loss and with at least 4 mo experience with BCD1 completed the study. Mean air-conduction and bone-conduction thresholds averaged across the frequencies of 500, 1000, 2000, and 4000 Hz were 73.9 and 34.2 dB HL, respectively.Data Collection and Analysis: Performance of the two devices was evaluated objectively by measuring aided free-field thresholds, speech perception in quiet, and speech perception in noise. A subjective evaluation was carried out with the Abbreviated Profile of Hearing Aid Benefit (APHAB) (Cox and Alexander, 1995) and the Speech, Spatial and Qualities of Hearing Scale (SSQ) questionnaire (Gatehouse and Noble, 2004). In addition, user experiences, user satisfaction, and device preference were obtained via proprietary questionnaires. Statistical significance was established with analysis-of-variance (ANOVA) and paired t-statistics with Bonferroni correction.Results: Aided free-field thresholds and speech reception thresholds (SRTs) in quiet were not statistically significantly different for either device (p > 0.05). In contrast, SRTs in noise were 2.0 dB lower (p < 0.001) for BCD2 than for BCD1. APHAB questionnaire scores on all subscales provided statistically significantly greater benefit (p < 0.05) for BCD2 than for BCD1. Also, with the SSQ most items in the speech and sound quality domain were significantly more favorable (p < 0.05) for BCD2 than for BCD1. Finally, all subjects preferred BCD2 over BCD1 with 14 subjects reporting a strong preference and four subjects an average preference for the digital signal processing provided by BCD2 over previous technology provided by BCD1.
Keywords: Assistive listening devices; auditory rehabilitation; hearing aids